The Impact of Safeguard Import Duty (BMTP) Policies and Macroeconomic Factors on Textile Import Volumes in Indonesia - I Gusti Ayu Agung Istri Dinda Larasshanti Jelantik; Komang Widhya Sedana Putra P (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyse the effectiveness of the Safeguard Import Duty or Bea Masuk Tindakan Pengamanan (BMTP) in controlling textile import volumes in Indonesia. It is also examining the influence of macroeconomic variables, exchange rates and inflation. This study is motivated by the increasing pressure from imports on the domestic textile industry and the need to evaluate trade defence policies in the context of developing countries. In this regard, the analysis integrates trade defence policies with exchange rate and inflation dynamics in order to better illustrate how macroeconomic conditions influence the outcomes of trade policies. A quantitative approach is employed using panel data regression, combining cross-sectional data from 14 countries and times series data from January 2019 to December 2025. The data are analyzed using a Fixed Effect Model (FEM) with robust standard errors to ensure reliable estimation. The results show that the countries subjected to safeguard policy (BMTP) is associated with lower import volumes, even though the effect is not statistically significant. Meanwhile, exchange rates and inflation have a positive and significant impact on import volume, indicating that macroeconomic conditions play a crucial role in shaping import dynamics. Simultaneously, all variables significantly affect import volume, highlighting the interaction between safeguard policy and macroeconomic factors. These results indicate that the effectiveness of trade policy cannot be separated from macroeconomic context. These findings contribute to the literature by providing empirical evidence on the limited effectiveness of trade protection policies when not supported by stable macroeconomic stability and industrial development. Practically, the study suggests that policymakers should complement protectionist measures with macroeconomic strategies and industrial capacity building.